2019
DOI: 10.1002/jbm.b.34314
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stent capable of the controlled release of basic fibroblast growth factor and argatroban to treat cerebral aneurysms: In vitro experiment and evaluation in a rabbit aneurysm model

Abstract: An ideal stent to treat cerebral aneurysms should have an antithrombotic effect on the inner stent blood-facing side and a tissue organization effect on the outer aneurysmal side of the stent. The objective of this study is to evaluate the feasibility of a drug containing stent in the in vivo treatment of cerebral aneurysms. Argatroban, an antithrombotic drug, is encapsulated in biodegradable poly (D,L-lactide-co-glycolide) (PLGA) microspheres for the controlled release with an in vitro study conducted to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, this composite induced diffuse foreign body reactions and granulocytic inflammations in porcine animal models, thereby posing a barrier for in vivo implantation [190]. Arai and colleagues [191] encapsulated basic fibroblast growth factor (bFGF) and agratroban in the PLGA coating of a metallic stent and tested it in a rabbit model to positively overcome the effect of an induced aneurysm. To the best of our knowledge, the only in vivo study of a prosthetic cardiac valve made of polyglycolic acid and polylactic acid in a 50:50 ratio was reported by Gottlieb and colleagues in a sheep model [192].…”
Section: Bioplastics Polymers As Implants In Vivomentioning
confidence: 99%
“…However, this composite induced diffuse foreign body reactions and granulocytic inflammations in porcine animal models, thereby posing a barrier for in vivo implantation [190]. Arai and colleagues [191] encapsulated basic fibroblast growth factor (bFGF) and agratroban in the PLGA coating of a metallic stent and tested it in a rabbit model to positively overcome the effect of an induced aneurysm. To the best of our knowledge, the only in vivo study of a prosthetic cardiac valve made of polyglycolic acid and polylactic acid in a 50:50 ratio was reported by Gottlieb and colleagues in a sheep model [192].…”
Section: Bioplastics Polymers As Implants In Vivomentioning
confidence: 99%
“…The results showed that the majority of the aneurysm cavity was occupied by loose connective tissues in the drug-coated stent group, whereas extensive massive hematomas were observed in the drug-free stent group. Moreover, the drug-coated stents had a relatively low rate of instent thrombosis (30). However, the feasibility and safety of drugcoated stents for the treatment of human intracranial aneurysms still needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Arai et al developed a stent that can control the release of basic fibroblast growth factor (bFGF) and biodegradable poly(D,L-lactide-co-glycolide) (PLGA) argatroban to accelerate the recovery of an aneurysm in the elastase rabbit model. The authors found that the occurrence rate of an in-stent thrombus is low in drugcoated stents, which may be used in the clinic in future (68). In addition to developing new devices, animal models are more commonly used to study the biological mechanics of aneurysm formation.…”
Section: Aneurysm Mechanism Explorationmentioning
confidence: 99%